2007
DOI: 10.1021/jp0666030
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission of a Single In-Doped ZnO Nanowire

Abstract: In-doped ZnO nanowires were successfully fabricated by thermal evaporation of a powder mixture of Zn, In2O3, and graphite. Field emission of individual In-doped and pure ZnO nanowire was observed in situ by a transmission electron microscopy. The results show that In-doped ZnO nanowires showed an enhanced field emission properties. First-principle density functional calculations were performed to calculate the electronic structure of the In-doped and pure ZnO in order to explain the observed field emission pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 21 publications
(43 reference statements)
3
57
0
Order By: Relevance
“…[31] Doping creates additional energy levels within the bandgap of a semiconductor and thus reduces the effective f. ZnO nanostructures are usually doped with trivalent metal atoms such as Ga and Al in order to improve their FE characteristics. [32] Encouraged by these studies, we have investigated for the first time, the effect of anion doping on the FE characteristics of ZnO nanostructures. Our investigations establish that N doping in ZnO can improve an FE current up to an order of magnitude.…”
Section: Field-emission Propertiesmentioning
confidence: 99%
“…[31] Doping creates additional energy levels within the bandgap of a semiconductor and thus reduces the effective f. ZnO nanostructures are usually doped with trivalent metal atoms such as Ga and Al in order to improve their FE characteristics. [32] Encouraged by these studies, we have investigated for the first time, the effect of anion doping on the FE characteristics of ZnO nanostructures. Our investigations establish that N doping in ZnO can improve an FE current up to an order of magnitude.…”
Section: Field-emission Propertiesmentioning
confidence: 99%
“…Moreover, due to its superior conducting properties, ZnO has also been investigated as a transparent conducting and piezoelectric material for use as electrodes, catalysts and sensors [3][4][5]. Recently, various doped ZnO nanostructures with different elements have been achieved to improve the electrical, optical and magnetic properties [6][7][8][9]. It was reported that the Sn-doping induces an emission at blue wavelength region [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that doping impurities, especially group III elements, such as Al [4], Ga [5], In [6], can significantly enhance the electrical conductivity and influence the optical properties. In order to generate desirable electrical, optical, and catalytic properties, 1D ZnO nanostructures have been doped with selected elements.…”
Section: Introductionmentioning
confidence: 99%